A Prospective Study of Diffusion-weighted Magnetic Resonance Imaging as an Early Prognostic Biomarker in Chemoradiotherapy in Squamous Cell Carcinomas of the Anus. Issue 12 (December 2020) - Muirhead, R.; Bulte, D.; Cooke, R.; Chu, K.-Y.; Durrant, L.; Goh, V.; Jacobs, C.; Ng, S.M.; Strauss, V.Y.; Virdee, P.S.; Qi, C.; Hawkins, M.A.
Abstract: Aims: The use of diffusion-weighted magnetic resonance imaging (DW-MRI) as a prognostic marker of treatment response would enable early individualisation of treatment. We aimed to quantify the changes in mean apparent diffusion coefficient (ΔADCmean ) between a DW-MRI at diagnosis and on fraction 8–10 of chemoradiotherapy (CRT) as a biomarker for cellularity, and correlate these with anal squamous cell carcinoma recurrence. Materials and methods: This prospective study recruited patients with localised anal cancer between October 2014 and November 2017. DW-MRI was carried out at diagnosis and after fraction 8–10 of radical CRT. A region of interest was delineated for all primary tumours and any lymph nodes >2 cm on high-resolution T2 -weighted images and propagated to the ADC map. Routine clinical follow-up was collected from Nation Health Service electronic systems. Results: Twenty-three of 29 recruited patients underwent paired DW-MRI scans. Twenty-six regions of interest were delineated among the 23 evaluable patients. The median (range) tumour volume was 13.6 cm 3 (2.8–84.9 cm 3 ). Ten of 23 patients had lesions with ΔADCmean ≤ 20%. With a median follow-up of 41.2 months, four patients either failed to have a complete response to CRT or subsequently relapsed. Three of four patients with disease relapse had lesions demonstrating ΔADCmean <20%, the other patient with persistent disease had ΔADCmean of 20.3%. Conclusions: We demonstrated a potential correlation between patients with ΔADCmean <20% and disease relapse. Further investigation of the prognostic merit of DW-MRI change is needed in larger, prospective cohorts. Highlights: It is feasible to perform serial DW-MRI scans on patients undergoing radical chemoradiotherapy. All patients who had disease recurrence showed a poor resolution of ΔADCMean in the second week of treatment. DW-MRI scans have potential to be used as imaging biomarkers of early response in anal squamous cell carcinoma. Further investigation is required in larger datasets.